Impact of non-pharmaceutical interventions targeted at COVID-19 pandemic on influenza burden – a systematic review (2020)
Objectives: To better understand the impact of comprehensive COVID-19 targeted nonpharmaceutical interventions (NPIs) on influenza burden worldwide. Methods: We conducted a systematic literature search in selected databases (PubMed, WHO COVID-19), preprint servers (medRxiv, bioRxiv) and websites of European Public Health institutes. Documents that compared influenza estimates in the 2019/2020 season with previous seasons were included. Information synthesis was qualitative due to a high heterogeneity in the number and periods of comparative seasons, outcome measures and statistical methods. Results: We included 23 records reporting from 15 countries/regions as well as 8 reports from European Public Health agencies. Estimates in the 2019/2020 season based on influenza virus tests (4 out of 7 countries/regions), defined influenza cases (8 out of 9), influenza positivity rate (7 out of 8), and severe complications (1 out of 2) were lower than in former seasons. Results from syndromic indicators, such as influenza-like-illness (ILI), were less clear or even raised (4 out of 7) after the influenza season indicating a misclassification with COVID-19 cases. Conclusions: Evidence synthesis suggests that NPIs targeted at SARS-CoV-2-transmission reduce influenza burden as well. Low threshold NPIs need to be more strongly emphasized in influenza prevention strategies.